Remotely Perceived: Investigating the Influence of Valence on Self-Perception and Social Experience for Dyadic Video-Conferencing With Personalized Avatars - Higgins, Darragh; Fribourg, Rebecca; McDonnell, Rachel (Frontiers in Virtual Reality, 2021)
Avatar use on video-conference platforms has found dual purpose in recent times as a potential method for ensuring privacy and improving subjective engagement with remote meeting, provided one can also ensure a minimal loss in the quality of social interaction and sense of personal presence. This work focuses on interaction through real-time motion captured virtual avatars in a video conferencing context. Our experiments were designed with the intention of exploring previously defined perceptual illusions that occur with avatar-use in Virtual and Augmented Reality settings. The research described here was aimed at empirically evaluating three separate dimensions of human-avatar interaction. The first was humans-as-avatars, with experimental conditions that were designed to measure changes to subjective perceptions of self-face ownership and self-concept. The second focus was other-perception, with the unique design of the studies outlined below among the first to measure social presence in a video-call between two human-driven avatars. The third emphasis was on the experiential content involved in avatar use, as there were measurements for emotion induction, fatigue and behaviour change included in the data collection. The results describe some evidence for face and body ownership, while participants also reported high levels of social presence with the other avatar, indicating that avatar cameras could be a favorable alternative to non-camera feeds in video conferencing. There were also some useful insights gained regarding emotion elicitation in non-video vs avatar conditions, as well as avatar-induced behaviour change.